Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Different temperature responses of mountain rockwalls, soils, and lakes to summer heat waves - Rosalie Bruel; Florent Arthaud; Florence Magnin; Raphaëlle Napoleoni; Colin Van Reeth; Vincent Augé; Clotilde Sagot; Mathieu Fructus; Carole Birck; Philippe Choler (Regional Environmental Change, 2026)
Mountain ecosystems are highly sensitive to climate variations. At fine spatial scales, high-elevation microclimates play a critical role in shaping biodiversity, hydrological processes, and ecosystem services, while also influencing the occurrence of natural hazards such as landslides, avalanches, and floods. Heat waves, which have been increasing in frequency and intensity due to global climate change, present significant challenges to these vulnerable environments. This study examines the impacts of summer heat waves on mountain microthermal conditions in three compartments: rockwalls, soils, and lakes. We assembled data across a latitudinal and elevational gradient in the French Alps including years of two recent heat wave events (2015 and 2022). We calculated thermal indicators to evaluate the buffering or amplifying effects of the atmospheric signal on the investigated compartments. The average summer temperature and the growing/thawing degree days were more responsive to heat waves than the phenological indicator (e.g., spring mixing date in lakes) and maximum temperature. We found significant anomalies for both the 2015 and 2022 heat waves across almost all compartments and indicators. Lakes tended to amplify atmospheric temperatures (especially in 2022) whereas rockwalls and soils tended to buffer them. However, residues from the relationship between compartment and atmospheric temperatures were large during heat waves, suggesting that these events may reduce the compartments’ buffering capacity. Our study underscores the importance of long-term monitoring of microthermal conditions to provide a more integrative assessment of mountain ecosystem response to extreme meteorological events. Graphical abstract

Leaf litter chemistry contributes to shape the chemical footprint of macrodetritivore communities - Théo Marchand; Matthieu Chauvat; Estelle Forey; Florence Maunoury-Danger; Mathieu Santonja; Michaël Danger; Philippe Usseglio-Polatera; David Baqué; Frédéric Candaudap; Sophia V. Hansson; Frédéric Julien; Christophe Laplanche; et al. (Applied Soil Ecology, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Cognitive and neuroimaging outcome of very prodromal dementia with Lewy bodies - Frédéric Blanc; Vincent Bouteloup; Claire Paquet; Marie Chupin; Florence Pasquier; Audrey Gabelle; Mathieu Ceccaldi; Paulo Loureiro de Sousa; Pierre Krolak-Salmon; Renaud David; Clara Fischer; Jean-François Dartigues; et al. (GeroScience, 2025)

Thermal treatment of sewage sludge: Impact of the sludge type and origin on the formation of recalcitrant compounds - Sylvain Faixo; Jean-Christophe Garrigues; Mathieu Haddad; Sofiane Mazeghrane; Gilberte Gaval; Florence Benoit-Marquié; Etienne Paul (Water Research, 2025)

Technosols made of urban wastes are suitable habitats for flora and soil macrofauna - Charlotte Pruvost; Jérôme Mathieu; Jeanne Vallet; Florence Dubs; Agnès Gigon; Thomas Lerch; Manuel Blouin (Ecological Engineering, 2025)

A continuous approach of modeling tumorigenesis and axons regulation for the pancreatic cancer - Marie-Jose Chaaya; Sophie Chauvet; Florence Hubert; Fanny Mann; Mathieu Mezache; Pierre Pudlo (Journal of Theoretical Biology, 2024)

In-vitro antibacterial and antibiofilm activities and in-silico analysis of a potent cyclic peptide from a novel Streptomyces sp. strain RG-5 against antibiotic-resistant and biofilm-forming pathogenic bacteria - El-Hadj Driche; Boubekeur Badji; Florence Mathieu; Abdelghani Zitouni (Archives of Microbiology, 2024)

Acyclovir treatment of varicella-zoster virus meningeal infections and acute kidney injury: a multicentre case series study - Myriam Contamine; Florence Ader; Quentin Lepiller; Benoit Martha; Joséphine Cagnon-Chapalain; Paul Leturnier; Emilie Frober; Kevin Bouiller; Christine Binquet; Christelle Auvray; Lionel Piroth; Mathieu Blot (Infectious Diseases, 2024)

Study of humic-like substances of dissolved organic matter using size exclusion chromatography and chemometrics - Sylvain Faixo; Romain Capdeville; Sofiane Mazeghrane; Mathieu Haddad; Gilberte Gaval; Etienne Paul; Florence Benoit-Marquié; Jean-Christophe Garrigues (Journal of Environmental Management, 2024)

Assessing the environmental impacts of conventional and organic scenarios of rainbow trout farming in France - Simon Pouil; Mathieu Besson; Florence Phocas; Joël Aubin (Journal of Cleaner Production, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

More than agriculture: Analysing time-cumulative human impact on European land-cover of second half of the Holocene - Anhelina Zapolska; Maria Antonia Serge; Florence Mazier; Aurélien Quiquet; Hans Renssen; Mathieu Vrac; Ralph Fyfe; Didier M. Roche (Quaternary Science Reviews, 2023)

Tumorigenesis and axons regulation for the pancreatic cancer: A mathematical approach - Sophie Chauvet; Florence Hubert; Fanny Mann; Mathieu Mezache (Journal of Theoretical Biology, 2023)

A New Saharan Strain of Streptomyces sp. GSB-11 Produces Maculosin and N-acetyltyramine Active Against Multidrug-Resistant Pathogenic Bacteria - El Hadj Driche; Boubekeur Badji; Christian Bijani; Saïd Belghit; Frédéric Pont; Florence Mathieu; Abdelghani Zitouni (Current Microbiology, 2022)

Saccharothrix algeriensis NRRL B-24137, the first non-Streptomyces actinobacterium, produces holomycin after cystine feeding - Rabiâa Merrouche; Amine Yekkour; Yannick Coppel; Noureddine Bouras; Abdelghani Zitouni; Florence Mathieu; Nasserdine Sabaou (Archives of Microbiology, 2020)

Providing Integrated Total Catch Advice for the Management of Mixed Fisheries with an Eco-viability Approach - Florence Briton; Claire Macher; Mathieu Merzeréaud; Christelle Le Grand; Spyros Fifas; Olivier Thébaud (Environmental Modeling & Assessment, 2020)
Well-established single-species approaches are not adapted to the management of mixed fisheries where multiple species are simultaneously caught in unselective fishing operations. In particular, ignoring joint production when setting total allowable catches (TACs) for individual species is likely to lead to over-quota discards or, when discards are not allowed, to lost fishing opportunities. Furthermore, economic and social objectives have been poorly addressed in the design of fisheries harvest strategies, despite being an explicit objective of ecosystem-based fisheries management in many jurisdictions worldwide. We introduce the notion of operating space as the ensemble of reachable, single-species fishing mortality targets, given joint production in a mixed fishery. We then use the concept of eco-viability to identify TAC combinations which simultaneously account for multiple objectives. The approach is applied to the joint management of hake and sole fishing in the Bay of Biscay, also accounting for catches of Norway lobster, European seabass and anglerfish. Results show that fishing at the upper end of the MSY range for sole and slightly above Fmsy for hake can generate gains in terms of long-term economic viability of the fleets without impeding the biological viability of the stocks, nor the incentives for crews to remain in the fishery. We also identify reachable fishing mortality targets in the MSY ranges for these two species, given existing technical interactions.

Impact of Spray-Drying on Biological Properties of Chitosan Matrices Supplemented with Antioxidant Fungal Extracts for Wine Applications - Elodie Choque; Vanessa Durrieu; Isabelle Alric; José Raynal; Florence Mathieu (Current Microbiology, 2020)

Broadcast spawning in Porites lutea at Reunion Island (Western Indian Ocean) - Lola M. Massé; Armand Daydé; Mathieu G. Séré; Florence Trentin (Western Indian Ocean Journal of Marine Science, 2019)
This study report in situ observations of broadcast spawning of P. lutea on a shallow reef flat of Reunion Island.

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Biodiversity loss along a gradient of deforestation in Amazonian agricultural landscapes - Thibaud Decaëns; Marlúcia B. Martins; Alexander Feijoo; Johan Oszwald; Sylvain Dolédec; Jérôme Mathieu; Xavier Arnaud de Sartre; Diego Bonilla; George G. Brown; Yeimmy Andrea Cuellar Criollo; Florence Dubs; Ivaneide S. Furtado; et al. (Conservation Biology, 2018)
Assessing how much management of agricultural landscapes, in addition to protected areas, can offset biodiversity erosion in the tropics is a central issue for conservation that still requires cross‐taxonomic and landscape‐scale studies. We measured the effects of Amazonia deforestation and subsequent land‐use intensification in 6 agricultural areas (landscape scale), where we sampled plants and 4 animal groups (birds, earthworms, fruit flies, and moths). We assessed land‐use intensification with a synthetic index based on landscape metrics (total area and relative percentages of land uses, edge density, mean patch density and diversity, and fractal structures at 5 dates from 1990 to 2007). Species richness decreased consistently as agricultural intensification increased despite slight differences in the responses of sampled groups. Globally, in moderately deforested landscapes species richness was relatively stable, and there was a clear threshold in biodiversity loss midway along the intensification gradient, mainly linked to a drop in forest cover and quality. Our results suggest anthropogenic landscapes with high‐quality forest covering >40 % of the surface area may prevent biodiversity loss in Amazonia.

De-escalation and discontinuation strategies in high-risk neutropenic patients: an interrupted time series analyses of antimicrobial consumption and impact on outcome - Giulia la Martire; Christine Robin; Nadia Oubaya; Raphaël Lepeule; Florence Beckerich; Mathieu Leclerc; Walid Barhoumi; Andréa Toma; Cécile Pautas; Sébastien Maury; Wiem Akrout; Catherine Cordonnier-Jourdin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Streptomyces sp. AT37 isolated from a Saharan soil produces a furanone derivative active against multidrug-resistant Staphylococcus aureus - El Hadj Driche; Nasserdine Sabaou; Christian Bijani; Abdelghani Zitouni; Frédéric Pont; Florence Mathieu; Boubekeur Badji (World Journal of Microbiology and Biotechnology, 2017)

Short-term and long-term survival of interval breast cancers taking into account prognostic features - Solenne Delacour-Billon; Anne Laure Mathieu-Wacquant; Mario Campone; Nathalie Auffret; Sophie Amossé; Corinne Allioux; Anne Cowppli-Bony; Florence Molinié (Cancer Causes & Control, 2017)

Design and validation of MEDRYS, a Mediterranean Sea reanalysis over the period 1992–2013 - Mathieu Hamon; Jonathan Beuvier; Samuel Somot; Jean-Michel Lellouche; Eric Greiner; Gabriel Jordà; Marie-Noëlle Bouin; Thomas Arsouze; Karine Béranger; Florence Sevault; Clotilde Dubois; Marie Drevillon; et al. (Ocean Science, 2016)
The French research community in the Mediterranean Sea modeling and the French operational ocean forecasting center Mercator Océan have gathered their skill and expertise in physical oceanography, ocean modeling, atmospheric forcings and data assimilation to carry out a MEDiterranean sea ReanalYsiS (MEDRYS) at high resolution for the period 1992–2013. The ocean model used is NEMOMED12, a Mediterranean configuration of NEMO with a 1∕12° ( ∼ 7 km) horizontal resolution and 75 vertical z levels with partial steps. At the surface, it is forced by a new atmospheric-forcing data set (ALDERA), coming from a dynamical downscaling of the ERA-Interim atmospheric reanalysis by the regional climate model ALADIN-Climate with a 12 km horizontal and 3 h temporal resolutions. This configuration is used to carry a 34-year hindcast simulation over the period 1979–2013 (NM12-FREE), which is the initial state of the reanalysis in October 1992. MEDRYS uses the existing Mercator Océan data assimilation system SAM2 that is based on a reduced-order Kalman filter with a three-dimensional (3-D) multivariate modal decomposition of the forecast error. Altimeter data, satellite sea surface temperature (SST) and temperature and salinity vertical profiles are jointly assimilated. This paper describes the configuration we used to perform MEDRYS. We then validate the skills of the data assimilation system. It is shown that the data assimilation restores a good average temperature and salinity at intermediate layers compared to the hindcast. No particular biases are identified in the bottom layers. However, the reanalysis shows slight positive biases of 0.02 psu and 0.15 °C above 150 m depth. In the validation stage, it is also shown that the assimilation allows one to better reproduce water, heat and salt transports through the Strait of Gibraltar. Finally, the ability of the reanalysis to represent the sea surface high-frequency variability is shown.

A complete hydro-climate model chain to investigate the influence of sea surface temperature on recent hydroclimatic variability in subtropical South America (Laguna Mar Chiquita, Argentina) - Magali Troin; Mathieu Vrac; Myriam Khodri; Daniel Caya; Christine Vallet-Coulomb; Eduardo Piovano; Florence Sylvestre (Climate Dynamics, 2016)

Thermoactinomyces khenchelensis sp. nov., a filamentous bacterium isolated from soil sediment of a terrestrial hot spring - Salim Mokrane; Noureddine Bouras; Atika Meklat; Abdelhadi Lahoum; Abdelghani Zitouni; Carol Verheecke; Florence Mathieu; Peter Schumann; Cathrin Spröer; Nasserdine Sabaou; Hans-Peter Klenk (Antonie van Leeuwenhoek, 2016)

Actinomadura algeriensis sp. nov., an actinobacterium isolated from Saharan soil - Abdelhadi Lahoum; Noureddine Bouras; Florence Mathieu; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Antonie van Leeuwenhoek, 2016)

Biocontrol Capacities and Plant Growth-Promoting Traits of Endophytic Actinobacteria Isolated from Native Plants of Algerian Sahara - Miyada Zamoum; Yacine Goudjal; Nasserdine Sabaou; Mustapha Barakate; Florence Mathieu; Abdelghani Zitouni (Journal of Plant Diseases and Protection, 2015)

Deoxynivalenol-producing ability of Fusarium culmorum strains and their impact on infecting barley in Algeria - Amine Yekkour; Omrane Toumatia; Atika Meklat; Carol Verheecke; Nasserdine Sabaou; Abdelghani Zitouni; Florence Mathieu (World Journal of Microbiology and Biotechnology, 2015)

Nocardiopsis algeriensis sp. nov., an alkalitolerant actinomycete isolated from Saharan soil - Noureddine Bouras; Atika Meklat; Abdelghani Zitouni; Florence Mathieu; Peter Schumann; Cathrin Spröer; Nasserdine Sabaou; Hans-Peter Klenk (Antonie van Leeuwenhoek, 2015)

Occurrence of 1,1′-dimethyl-4,4′-bipyridinium (Paraquat) in irrigated soil of the Lake Chad Basin, Niger - Marc Crampon; Yoann Copard; Guillaume Favreau; Julie Raux; Nadine Merlet-Machour; Mathieu Le Coz; Maïmouna Ibrahim; Valérie Peulon-Agasse; Florence Portet-Koltalo (Environmental Science and Pollution Research, 2014)

Streptomonospora algeriensis sp. nov., a halophilic actinomycete isolated from soil in Algeria - Atika Meklat; Noureddine Bouras; Amar Riba; Abdelghani Zitouni; Florence Mathieu; Manfred Rohde; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Antonie van Leeuwenhoek, 2014)

The Saharan isolate Saccharothrix algeriensis NRRL B-24137 induces systemic resistance in Arabidopsis thaliana seedlings against Botrytis cinerea - Saima Muzammil; Clotilde Graillon; Rayenne Saria; Florence Mathieu; Ahmed Lebrihi; Stéphane Compant (Plant and Soil, 2014)

Endophytic actinomycetes from spontaneous plants of Algerian Sahara: indole-3-acetic acid production and tomato plants growth promoting activity - Yacine Goudjal; Omrane Toumatia; Nasserdine Sabaou; Mustapha Barakate; Florence Mathieu; Abdelghani Zitouni (World Journal of Microbiology and Biotechnology, 2013)

Visualization of grapevine root colonization by the Saharan soil isolate Saccharothrix algeriensis NRRL B-24137 using DOPE-FISH microscopy - Stéphane Compant; Saima Muzammil; Ahmed Lebrihi; Florence Mathieu (Plant and Soil, 2013)

Actinopolyspora righensis sp. nov., a novel halophilic actinomycete isolated from Saharan soil in Algeria - Atika Meklat; Noureddine Bouras; Abdelghani Zitouni; Florence Mathieu; Ahmed Lebrihi; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Antonie van Leeuwenhoek, 2013)

Use of beneficial bacteria and their secondary metabolites to control grapevine pathogen diseases - Stéphane Compant; Günter Brader; Saima Muzammil; Angela Sessitsch; Ahmed Lebrihi; Florence Mathieu (BioControl, 2013)

Comprehensive Functional Mapping Scheme for Non-Invasive Primary Sensorimotor Cortex Mapping - Mathieu Bourguignon; Veikko Jousmäki; Brice Marty; Vincent Wens; Marc Op de Beeck; Patrick Van Bogaert; Mustapha Nouali; Thierry Metens; Boris Lubicz; Florence Lefranc; Michael Bruneau; Olivier De Witte; et al. (Brain Topography, 2013)

Actinopolyspora saharensis sp. nov., a novel halophilic actinomycete isolated from a Saharan soil of Algeria - Atika Meklat; Noureddine Bouras; Abdelghani Zitouni; Florence Mathieu; Ahmed Lebrihi; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Antonie van Leeuwenhoek, 2013)

The effects of snowpack properties and plant strategies on litter decomposition during winter in subalpine meadows - Patrick Saccone; Samuel Morin; Florence Baptist; Jean-Marc Bonneville; Marie-Pascale Colace; Florent Domine; Mathieu Faure; Roberto Geremia; Jonathan Lochet; Franck Poly; Sandra Lavorel; Jean-Christophe Clément (Plant and Soil, 2013)

Actinopolyspora algeriensis sp. nov., a novel halophilic actinomycete isolated from a Saharan soil - Atika Meklat; Noureddine Bouras; Abdelghani Zitouni; Florence Mathieu; Ahmed Lebrihi; Peter Schumann; Cathrin Spröer; Hans-Peter Klenk; Nasserdine Sabaou (Extremophiles, 2012)

The 125th anniversary of the first postulation of the soil origin of endophytic bacteria – a tribute to M.L.V. Galippe - Stéphane Compant; Angela Sessitsch; Florence Mathieu (Plant and Soil, 2012)

Saccharothrix sp. PAL54, a new chloramphenicol-producing strain isolated from a Saharan soil - Adel Aouiche; Nasserdine Sabaou; Atika Meklat; Abdelghani Zitouni; Christian Bijani; Florence Mathieu; Ahmed Lebrihi (World Journal of Microbiology and Biotechnology, 2012)

Brain Regional Glucose Uptake Changes in Isolated Cerebellar Cortical Dysplasia: Qualitative Assessment Using Coregistrated FDG-PET/MRI - Patrice Jissendi-Tchofo; Florence Pandit; Louis Vallée; Mathieu Vinchon; Jean-Pierre Pruvo; Danielle Baleriaux; Gustavo Soto Ares (The Cerebellum, 2012)

Purification and structure elucidation of three naturally bioactive molecules from the new terrestrial Streptomyces sp. TN17 strain - Slim Smaoui; Lotfi Mellouli; Ahmed Lebrihi; Yannick Coppel; Lilia Fourati Ben Fguira; Florence Mathieu (Natural Product Research, 2011)

Consequences of prolonged total thermoneutral immersion on muscle performance and EMG activity - Mathieu Coulange; Florence Riera; Bruno Melin; Stephane Delliaux; Nathalie Kipson; Chantal Gimenez; Claude Robinet; Yves Jammes (Pflügers Archiv - European Journal of Physiology, 2008)

Characteristics and Genetic Determinants of Bacteriocin Activities Produced by Carnobacterium piscicola CP5 Isolated from Cheese - Sabine Herbin; Florence Mathieu; Fabienne Brulé; Christiane Branlant; Gérard Lefebvre; Ahmed Lebrihi (Current Microbiology, 1997)